2011
DOI: 10.3354/meps09224
|View full text |Cite
|
Sign up to set email alerts
|

Growth in the brown shrimp Crangon crangon. II. Meta-analysis and modelling

Abstract: Existing laboratory and field data on growth were combined, reanalyzed and discussed to generate a holistic temperature-, length-and gender-dependent growth rate (G, mm d -1 ) model for North Sea region brown shrimp Crangon crangon (L.). Length (L, mm) and temperature (T, °C) dependent growth rates of Crangon crangon are highly variable within and among studies but decrease with L and increase with T. Applying general nonlinear regression, mean growth was derived as G = 0.02421·T -0.00115·e 0.08492·T · L … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
29
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(33 citation statements)
references
References 66 publications
3
29
1
Order By: Relevance
“…But contrasting to our finding, a positive correlation was observed in lobsters between a period of rising seawater temperature and (epizootic) shell disease prevalence (Castro et al, 2006;Glenn and Pugh, 2006;Tlusty and Metzler, 2012). In contrast to C. crangon, lobsters do not molt as often as shrimps and retain their shells for a longer timescale (Hufnagl and Temming, 2011b;Hughes and Matthiessen, 1962). Therefore, it might be possible that bacteria living on lobster shells have more time to cause shell disease.…”
Section: Discussioncontrasting
confidence: 56%
See 2 more Smart Citations
“…But contrasting to our finding, a positive correlation was observed in lobsters between a period of rising seawater temperature and (epizootic) shell disease prevalence (Castro et al, 2006;Glenn and Pugh, 2006;Tlusty and Metzler, 2012). In contrast to C. crangon, lobsters do not molt as often as shrimps and retain their shells for a longer timescale (Hufnagl and Temming, 2011b;Hughes and Matthiessen, 1962). Therefore, it might be possible that bacteria living on lobster shells have more time to cause shell disease.…”
Section: Discussioncontrasting
confidence: 56%
“…Each organism has its optimum temperature which is defined as the point at which the reaction rate and physiological performances is maximal (Angilletta et al, 2002;Reiser et al, 2014). Comparing the effect of temperature on the growth rates of C. crangon in various studies, Hufnagl and Temming (2011b) observed that the optimal temperature range of adult brown shrimp was between 18 and 22°C. Also Tiews (1970) mentioned a similar optimal temperature range for C. crangon of 15-20°C and Freitas et al (2007) determined 23°C as the optimum temperature.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This variability resulted in significant random effects (individual shrimps) in both models. Such considerable individual variability in growth patterns had previously been described for the same studied populations (Campos et al 2009), as well as for shrimps from the North Sea (Hufnagl & Temming 2011a) and from other locations (for a summary table see Hufnagl & Temming 2011b). As a consequence of this individual variability, field populations consist as a mix of fast-and slow-growing shrimps.…”
Section: Discussionmentioning
confidence: 95%
“…This species is very common and abundant in the shallow areas of the German Bight (Siegel et al 2008), plays an important role in the energy transfer within marine food webs (Pihl and Rosenberg 1984;Campos et al 2009) and sustains an important fishery with annual captures exceeding 35,000 tons (ICES 2010). The complex life cycle of C. crangon comprises a benthic juvenile-adult and a pelagic larval phase (Tiews 1970;Hufnagl and Temming 2011), which are tightly linked (Daewel et al 2011;Viegas et al 2012). It is thus necessary to also investigate traits of the early life-history phases, which may influence the population dynamics.…”
Section: Introductionmentioning
confidence: 99%